Stuart J. Fleming: Vinum. The Story of Roman Wine - Jaine, Tom (Petits Propos Culinaires, 2024)
Stuart J. Fleming: Vinum. The Story of Roman Wine: Art Flair, Glen Mills PA, 2001: ISBN 0971274207: 134 pp., many colour illus., h/b.